Development Strategy of Religious Culture at Madrasah Tsanawiyah Negeri 2, Mojokerto, East Java - Abd. Wahib (Journal of Islamic Education Research, 2023)
This research aims to describe the formulation, implementation, and evaluation of religious culture as the development of Islamic education in madrasa. This study uses a qualitative method and collects the data through observation techniques, interviews, and documentation. Data analysis uses data condensation techniques, data display, and conclusions. The results of this study are: (1) The formulation of religious culture is motivated by the existence of a community culture that needs to be internalized based on religious values so that it becomes a good habit. The purpose of religious culture from the spiritual aspect is to increase students' spirituality, and the social aspect is to shape students' character. (2) The implementation of religious culture includes "Friday Qur’an Recitation" by reciting Surah Yasin, "Friday Sedaqah," which is routinely held on Fridays after reciting Surah Yasin, and "S3TC culture" held every day when students enter the school gate and are greeted by the teachers. (3) Evaluation of the implementation of religious culture through evaluating attitudes and giving rewards and punishments.